The Effect of the Implementation of Islamic Religious Education and Religious Character on Independence for Class XI Students of SMA Negeri 3 Boyolali for the 2021/2022 Academic Year - Muhammad Syaifudin Zuhri; Muhammad Thoriqul Islam; Nurdiyanto Nurdiyanto; Nawa Marjany; Aynun Nurul Ulufah; Ulfi Usykuriyah Khoiry (Jurnal Syntax Transformation, 2024)
Islamic Religious Education (IRE) in schools plays a significant role in shaping individuals' religious values. A study was conducted to uncover the influence of IRE and religious character on the self-reliance of 11th-grade students at SMA Negeri 3 Boyolali in the academic year 2021/2022. A quantitative correlational method was employed with a population of 323 students. A sample of 20 individuals was selected using stratified simple random sampling. Data were collected through questionnaires and analyzed using descriptive methods, Product Moment correlation, regression, t-test, F-test, and R2 test. The research findings indicate that the implementation of IRE has a positive and significant effect on student self-reliance. Similarly, religious character has an equally significant influence on student self-reliance. Both factors contribute significantly to student self-reliance simultaneously. In conclusion, higher implementation of IRE and stronger religious character lead to increased self-reliance among 11th-grade students at SMA Negeri 3 Boyolali in the academic year 2021/2022.